2021
DOI: 10.1021/acschembio.1c00227
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a C-Glycosyltransferase Involved in Medermycin Biosynthesis

Abstract: C-Glycosylation in the biosynthesis of bioactive natural products is quite unique, which has not been studied well. Medermycin, as an antitumor agent in the family of pyranonaphthoquinone antibiotics, is featured with unique C-glycosylation. Here, a new C-glycosyltransferase (C-GT) Med-8 was identified to be essential for the biosynthesis of medermycin, as the first example of C-GT to recognize a rare deoxyaminosugar (angolosamine). med-8 and six genes (med-14, -15, -16, -17, -18, and -20 located in the mederm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…OUCMDZ-4982 was sequenced, and the medermycin biosynthetic gene cluster ( med cluster) in this strain was compared with the reported cluster from Streptomyces sp. AM-7161 37 , 38 . The med cluster in Streptomyces sp.…”
Section: Resultsmentioning
confidence: 99%
“…OUCMDZ-4982 was sequenced, and the medermycin biosynthetic gene cluster ( med cluster) in this strain was compared with the reported cluster from Streptomyces sp. AM-7161 37 , 38 . The med cluster in Streptomyces sp.…”
Section: Resultsmentioning
confidence: 99%
“…Alignment of the amino acid sequences of Kid7 and Kid21 with those of HedJ and HedL, respectively, also showed that the proteins are significantly identical (Kid7 vs. HedJ, 67.5% similarity; Kid21 vs. HedL, 71.8% similarity) ( Supplementary Table S4 ). Additionally, both Kid7 and Kid21 resemble Med-8 (52% and 59% similarity, respectively), a C-GT responsible for angolosamine transfer in medermycin biosynthesis ( Ichinose et al, 2003 ; Cai et al, 2021 ). However, Kid21 is believed to be responsible for angolosamine transfer, because of its high degree of identity with Med-8.…”
Section: Resultsmentioning
confidence: 99%
“…The late steps for angolosamine biosynthesis, which may be interchangeable, are catalyzed by 4′-keto-reductase and N-methyltransferase. The 4′-keto-reductase genes, med-ORF14 ( Cai et al, 2021 ) and gra-ORF22 ( Tornus and Floss, 2001 ), encode proteins 60% similar to the Kid23 enzyme. Kid4 is highly similar to AORI_1488 (76%), which catalyzes the C-methylation at aminohexose in the vancomycin biosynthetic pathway ( van Wageningen et al, 1998 ; Chen et al, 2000 ; Xu et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…C -Glycosylation is a unique phenomenon in nature and is involved in the bioactivity of natural products. Only a small number of biologically important natural products are C -glycosides ( Cai et al, 2021 ). In the mayamycin gene cluster, we predicted the presence of genes for a rare C -glycosyltransferase and biosynthesis of a rare deoxy-amino sugar (angolosamine), which will be confirmed functionally and used for combinatorial biosynthesis of glycosides, to enrich the structural and bioactivity diversification of these therapeutically important compounds.…”
Section: Discussionmentioning
confidence: 99%